Seni Mural Sebagai Elemen Estetik Pada Kafe di Jakarta (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2021)
This art review research for mural as aesthetic element at café in DKI Jakarta aim at knowing the whole function and benefits of art. Visit to café for the most of people in a modern lifestyle gives different experience. Beside people buying drinks and food society, visitor will get some education and information from various types of mural and the atmosphere at the café. This research is a descriptive qualitative with techniques of data collection including: observation, interviews, documentation and analysis of documents. The result of all the research data obtained, then reduced based on criteria of mural and completion of components at the café. Then the data is present and validate by the triangulation method, with two assessors in the same field. This research find facts that everyone has a different criteria and opinion when enjoying the aesthetic element of mural at the café. There are many cafes which follow trend of urban society and follows the up to date theme, alongside thinking about the food and comfort of the place. But on the other side, there are café that can not compete with other competitors, so the café is left behind. Beside, this research also recommends cafe entrepreneurs to develop their business to give visitors the best experience. By providing a pleasant atmosphere so that visitors do not feel bored and visitors will come back to the café because it feels comfortable and nice.